2014
DOI: 10.1016/j.ica.2013.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Vanadate complexes of 3-hydroxy-1,2-dimethyl-pyridinone: Speciation, structure and redox properties

Abstract: Several articles were published about the vanadate-3-hydroxy-1,2-dimethyl-pyridinone (Hdhp) system, however, the results are contradictory and not complete: pH-potentiometry and 51 V-NMR spectroscopy were used to clarify this complicated system. The eleven peaks in the spectra at different chemical shifts were assigned to ten stoichiometrically different compounds; four of them are new, never identified or assigned before. Besides the simple mono-(in two different protonation states) and bis complexes (in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
1
15
0
1
Order By: Relevance
“…The Rh(III) center exhibits a pseudo-octahedral geometry ("piano-stool"), and the Cp* moiety occupies facially three coordination sites, while the and angles between the metal center and the donor atoms were found in the same range as reported for related structures [28]. Proton dissociation equilibria of the studied ligands dhp and pic are well known in the literature [40][41][42], and pK a values determined by pH-potentiometry (see table 2) are in reasonably good agreement with data reported under identical conditions as used in this study [43,44] with the exception of dhp (at I = 0.20 M (KNO 3 )) where no data were available. [22,45].…”
Section: Synthesis Of Organometallic Rh(iii) Complexes and Characterisupporting
confidence: 51%
“…The Rh(III) center exhibits a pseudo-octahedral geometry ("piano-stool"), and the Cp* moiety occupies facially three coordination sites, while the and angles between the metal center and the donor atoms were found in the same range as reported for related structures [28]. Proton dissociation equilibria of the studied ligands dhp and pic are well known in the literature [40][41][42], and pK a values determined by pH-potentiometry (see table 2) are in reasonably good agreement with data reported under identical conditions as used in this study [43,44] with the exception of dhp (at I = 0.20 M (KNO 3 )) where no data were available. [22,45].…”
Section: Synthesis Of Organometallic Rh(iii) Complexes and Characterisupporting
confidence: 51%
“…Absorbance spectra were analyzed at λ > 310 nm, where neither the reduced nor the oxidized forms of GSH and ASC absorb light. 46,47 No significant spectral changes were observed upon reaction of the iron(III) complexes with 2.5 equivalents of GSH (in HEPES buffer, pH 7.4) within a time frame of 90 min. It was reported that the reduction of some iron(III) 47 and vanadium(V) 46,48 complexes by GSH might be kinetically hindered, while the dehydro-L-ascorbic acid/ASC redox pair (E′°at physiological pH = +0.05 V), 49 reacts considerably faster.…”
Section: Redox Properties Of the Studied 8-hydroxyquinolines With Iromentioning
confidence: 98%
“…Although it is generally accepted that vanadates increase the kinetics of CO 2 absorption, little is known about the mechanism associated with this process [35]. Both we [36] and others [37] have shown that a combination of 51 V NMR spectroscopy and potentiometric titrations are ideal for investigating the equilibria associated with the complex vanadate system. Here, we extend this work to incorporate the interaction of bicarbonate with the vanadate system.…”
Section: Introductionmentioning
confidence: 93%